Trabalho livre, trabalho escravo: experiências em comum - Negro, Antonio Luigi (Afro-Ásia, 2019)
Resenha de: MATTOS, Marcelo Badaró. Laborers and Enslaved Workers: Experiences in Common in the Making of Rio de Janeiro’s Working Class, 1850–1920. Nova York: Berghahn Books, 2017. 175p.